Liability of producers of goods and providers of services to e-consumers / Jawahitha Sarabdeen and Mohamed Ishak Mohamed Mazahir - Sarabdeen, Jawahitha; Mohamed Mazahir, Mohamed Ishak (2004)
The Malaysian laws protecting the e-consumers are still in the infant stage. A claim against a retailer could be maintained under certain legislation like the Contacts Act or Sale of Goods Act. When an e-consumer elects to sue a manufacturer or service provider, the only option available for him to do so would be under negligence tort. The spectrum of protection, however, is very much limited. The paper will analyze the negligence tort in protecting the e-consumers in a claim against the manufacturers and the service providers. It will also address the limitation of application of negligence together with the deficiencies of fault-based liability in providing appropriate protection for injured e consumer who is not actually at fault.